Comparative analyzes among electrical resistivity tomography arrays in the characterization of flow structure in free aquifer - Moreira, Cesar Augusto [UNESP]; Lapola, Marcelo Montenegro [UNESP]; Carrara, Alan [UNESP] (Inst Geophysics Unam, 2016)
This paper makes a comparative analysis between the Dipole-dipole, Wenner and Schlumberger arrays through electric resistivity tomography (ERT), about the sensitivity and resolution in the spatial characterization of infiltrating pollutants in septic tank and cone of depression in supply well, both contained in unconfined aquifer. Data acquisition consisted of electrical resistivity readings using five parallel lines with 105m long, electrode spacing and lines of 5m. The data from each line were subjected to 2D inversion and then interpolated to generate 3D blocks, which were extracted from a fixed resistivity isosurface (620 Omega.m), which enabled the modeling of volumes related to the flow structures. The results for the Dipole-dipole array allowed the modeling of the cylindrical structure associated to the supply well, and an isosurface deformation associated to the septic tank, but did not allow the modeling of the plume. The data for the Schlumberger array cannot allow for the cone recognition, but resulted in a drop shape model, associated to the septic tank and similar to a contamination plume. The Wenner array resulted in a model with structure in elongated keel format associated to the cone of depression, and another that is similar to the drop shape model, also associated to the septic tank. The comparative analysis shows that the Dipole-dipole array is recommended in works of modeling vertically integrated three-dimensional structures of high resistivity in the saturated zone. The Wenner and Schlumberger arrays are recommended for modeling vertically integrated three-dimensional structures of low resistivity in unsaturated zone, with emphasis on the Schlumberger array.
Keywords: Dipole-dipole; Schlumberger; Wenner; contamination plume; cone of depression